Sequencing activities in a project network with resource complementarity : further results - Silva, Hélder C. (2011)
We address the issue of optimal resource allocation, and more specifically, the analysis of complementarity of resources (primary resource or P-resource and supportive resource or S-resource) to activities in a project. In this paper we present new computational results of a Genetic Algorithm, based in a random keys alphabet.